2023
DOI: 10.3390/s23083810
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Counting of Apples in a Dynamic State Using a 3D Camera and Deep Learning Algorithms for Robotic Harvesting Systems

Abstract: Recognition and 3D positional estimation of apples during harvesting from a robotic platform in a moving vehicle are still challenging. Fruit clusters, branches, foliage, low resolution, and different illuminations are unavoidable and cause errors in different environmental conditions. Therefore, this research aimed to develop a recognition system based on training datasets from an augmented, complex apple orchard. The recognition system was evaluated using deep learning algorithms established from a convoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The proposed model tracking experiment was performed on three different videos, and the consolidated MAPE applying DeepSORT was 0.197 and our proposed model attained a low MAPE of 0.027. The DeepSORT [56] technique also provided almost near results, but the duplication of apples and background apples that were not measured for the series of sequence counts made the model vulnerable. However, ByteTrack along with the recommended detection method categorized the apples in the foreground and background and included only the targeted apples in the count.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed model tracking experiment was performed on three different videos, and the consolidated MAPE applying DeepSORT was 0.197 and our proposed model attained a low MAPE of 0.027. The DeepSORT [56] technique also provided almost near results, but the duplication of apples and background apples that were not measured for the series of sequence counts made the model vulnerable. However, ByteTrack along with the recommended detection method categorized the apples in the foreground and background and included only the targeted apples in the count.…”
Section: Discussionmentioning
confidence: 99%
“…A camera is also capable of distinguishing objects such as weeds and landmarks through image processing techniques [7]. The combination of deep learning algorithms with 3D cameras has made a significant contribution to object recognition, supporting robotic operations in orchards [6,8]. YOLO (You Only Look Once) is a highly efficient one-stage object detection model known for its speed, accuracy, and reliable real-time performance.…”
Section: Figurementioning
confidence: 99%
“…Even with a hand-held weed cutter, weeds around trees are still difficult to reach. In other cases, such as modern apple orchards, a V-shaped tree architecture is deployed to produce high-quality fruit and incorporates certain poles that can serve as obstacles for autonomous navigation [6]. A camera-attached small autonomous robotic weeder can be used to easily reach weeds while avoiding the obstacles present.…”
Section: Introductionmentioning
confidence: 99%
“…Different convolutional neural network (CNN)-based architectures, such as YOLOv3 [ 21 ], YOLOv5 [ 22 ], YOLOv7 [ 23 ], Faster RCNN [ 24 ], Mask RCNN [ 9 ], EfficientDet [ 25 ], and CenterNet, which have been trained based on apple datasets, have been used for detection and localization with high accuracy. Initially, 2D cameras were used as color sensors [ 26 , 27 ] to identify the apples, and the 2D information provided faced interference resulting from variations in light conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Intel ® RealSense™ D435 [ 1 ] and D455™ (Intel Corporation, Santa Clara, CA, USA) [ 25 ] cameras were used to localize the apples, and the grasping pose was estimated based on the processing point cloud obtained from depth streams [ 42 ], but the results showed average accuracies of 0.61 cm and 4.80° degrees from the center position and orientation, respectively. The previous study [ 25 ] that we conducted was based on the state of art (SOTA) of detection algorithms: YOLOv4, YOLOv5, YOLOv7, and EfficientDet combined with a RealSense D455 camera to measure the accuracy of apple detection in terms of depth values at the dynamic stage. According to the results, we found that EfficientDet outperforms with higher accuracy than other networks as regards other detection models, compared with the RMSE values.…”
Section: Related Workmentioning
confidence: 99%